A transcriptomic analysis of black cohosh: Actein alters cholesterol biosynthesis pathways and synergizes with simvastatin. (October 2018) - Einbond, Linda Saxe; Soffritti, Morando; Esposti, Davide Degli; Wu, Hsan-au; Balick, Michael; Ma, Hongbao; Redenti, Stephen; Roter, Alan
Abstract: Previous studies indicate that the herb black cohosh ( Actaea racemosa L.) and the triterpene glycoside actein inhibit the growth of human breast cancer cells and activate stress-associated responses. This study assessed the transcriptomic effects of black cohosh and actein on rat liver tissue, using Ingenuity and ToxFX analyses. Sprague-Dawley rats were treated with an extract of black cohosh enriched in triterpene glycosides (27%) for 24 h or actein for 6 and 24 h, at 35.7 mg/kg, and liver tissue collected for gene expression analysis. Ingenuity analysis indicates the top canonical pathways are, for black cohosh, RAR Activation, and, for actein, Superpathway of Cholesterol Biosynthesis, at 24 h. Actein alters the expression of cholesterol biosynthetic genes, but does not inhibit HMG-CoA reductase activity. Black cohosh and actein inhibited the growth of human breast and colon cancer cells and synergized with the statin simvastatin. Combinations of black cohosh with certain classes of statins could enhance their activity, as well as toxic, such as inflammatory liver, side effects. Transcriptomic analysis indicates black cohosh and actein warrant further study to prevent and treat cancer and lipid disorders. This study lays the basis for an approach to characterize the mode of action and toxicity of herbal medicines. Graphical abstract: Highlights: Transcriptomic analysis of effects of black cohosh and actein on rat liver tissue: Ingenuity Pathway and ToxFX analysis. Black cohosh alters Acute Phase Response Signaling at 24 h. Actein alters the Superpathway of Cholesterol Biosynthesis at 6 and 24 h. Actein does not inhibit HMG-CoA reductase activity. Black cohosh and actein inhibited the growth of colon cancer cells and synergized with the statin simvastatin.